2020
DOI: 10.1007/s11033-020-05246-4
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput retrotransposon-based genetic diversity of maize germplasm assessment and analysis

Abstract: Maize is one of the world's most important crops and a model for grass genome research. Long terminal repeat (LTR) retrotransposons comprise most of the maize genome; their ability to produce new copies makes them efficient high-throughput genetic markers. Inter-retrotransposon-amplified polymorphisms (IRAPs) were used to study the genetic diversity of maize germplasm. Five LTR retrotransposons (Huck, Tekay, Opie, Ji, and Grande) were chosen, based on their large number of copies in the maize genome, whereas p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…However, DNA profiling applications based on retrotransposons are limited by a paucity of knowledge about nucleotide sequences of LTR retrotransposons in species without a sequenced genome. In particular, phytopathogenic fungi have a small genome, so the development of genetic markers based on retrotransposons is difficult relative to species with a large genome (e.g., green plants and animals; Mandoulakani et al, 2015;Doungous et al, 2015;Ghonaim et al, 2020;Leigh et al, 2003;Li et al, 2020;Teo et al, 2005;Vukich et al, 2009;Vuorinen et al, 2018). However, the Inter-primer Binding Site (iPBS) amplification technique has proved to be a powerful DNA fingerprinting method that does not require information about retrotransposon sequences (Kalendar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, DNA profiling applications based on retrotransposons are limited by a paucity of knowledge about nucleotide sequences of LTR retrotransposons in species without a sequenced genome. In particular, phytopathogenic fungi have a small genome, so the development of genetic markers based on retrotransposons is difficult relative to species with a large genome (e.g., green plants and animals; Mandoulakani et al, 2015;Doungous et al, 2015;Ghonaim et al, 2020;Leigh et al, 2003;Li et al, 2020;Teo et al, 2005;Vukich et al, 2009;Vuorinen et al, 2018). However, the Inter-primer Binding Site (iPBS) amplification technique has proved to be a powerful DNA fingerprinting method that does not require information about retrotransposon sequences (Kalendar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphism in RBIP is usually detected by gel electrophoresis or hybridization, using agarose or dot assays respectively. In high-throughput RBIP analysis, data is obtained usually by fluorescent scoring from generated tagged microarray marker profiles ( Ghonaim et al., 2020 ). A major challenge with RBIP characterization is the need for information on sequence of sections adjoining the retrotransposon insertion sites.…”
Section: The Concept Of Molecular or Dna Markersmentioning
confidence: 99%
“…Similarly, molecular genotyping of sweet sorghum using SSR markers analyzed using NJ clustering method by Disasa et al (2014) showed the grouping of accessions based on geographical origin. Recently, Ghonaim et al (2020) in genetic diversity study of maize reported the clustering pattern resulted from retrotransposon data resulted in the grouping of samples based on ecogeographical origin. The structure of the dendrogram figuring out the clustering of 23 accessions into three groups with varying degree taxonomic distance showed high genotypic variability.…”
Section: Genotypic Variability and Relationships Of S Bicolor Accessmentioning
confidence: 99%